APAKAH PENGHINDARAN PAJAK PERUSAHAAN MENJELASKAN EFISIENSI INVESTASI? BUKTI DARI EKONOMI BERKEMBANG - Karunia, Putu Agus Ray; Darma, Gede Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.02.TAHUN.2022DO - 10.24843/EEB.2022.v11.i02.p05, 2022)
The purpose of this study is to determine whether corporate tax avoidance can explain efficiency in investment? Based on emerging economies. This study uses secondary data in the form of annual reports or financial statements of companies listed on the Indonesia Stock Exchange (IDX) and publications on the pages of each company. The research period is three years (2017-2019). This research uses descriptive statistical analysis and linear regression which is analyzed using EViews. The results of this study are the relationship of tax avoidance has a significant positive effect on investment inefficiency, then the quality of financial statements and corporate governance in the company has a significant negative effect on investment inefficiency. Good quality of financial reports as a moderating variable can weaken the relationship between tax avoidance and investment inefficiency. Meanwhile, the moderating effect of corporate governance on tax avoidance on investment inefficiency does not have a significant effect. This means that corporate governance does not weaken the relationship between tax avoidance and investment inefficiency.